A new comprehensive methodology for the evaluation of product sustainability at the design and development stage of consumer electronic products. (23rd March 2009) - De Silva, Niranjali; Jawahir, I.S.; Dillon Jr., Oscar; Russell, Matthew
This paper presents quantifiable sustainability elements in manufactured consumer electronic products. A 'Sustainability Scoring' method is introduced at the design stage. A new product can be evaluated using this method for its integral elemental and the overall sustainability contents impacting the product when it reaches the end-of-life by considering the entire life-cycle, including the effective residual use of recovered materials in the subsequent life-cycles of the same or different products. This procedure can also be used by design engineers for comparison with a similar product, such as a prior or a subsequent model, or one from a competitor.